Metagenomic and 13C tracing evidence for autotrophic atmospheric carbon absorption in a semiarid desert. (October 2018) - Liu, Zhen; Sun, Yanfei; Zhang, Yuqing; Feng, Wei; Lai, Zongrui; Fa, Keyu; Qin, Shugao
Abstract: Atmospheric carbon dioxide (CO2 ) absorption by desert soils has received increasing interests in recent years; however, the underlying physical and chemical mechanisms are not commonly acceptable. Here, we hypothesised that autotrophic carbon fixation of soil microbes contributes to this process. To test this postulate, we investigated the genomic and biochemical potential of autotrophic carbon fixation and traced atmospheric autotrophic carbon absorption using metagenomics and 13 CO2 labelling approaches in the Mu Us Desert in northern China. More than 30000 genes involved in the six carbon fixation pathways (approximately 2% of the assembled metagenomes, in relative abundance) were found in the metagenome of the desert soil, and the relative abundance for genes encoding for the reductive citrate cycle was the highest among the six pathways. The main autotrophic microbes employing the six pathways belong to Actinobacteria, Proteobacteria, Chloroflexi, Acidobacteria, Gemmatimonadetes, Firmicutes, Thaumarchaeota, Nitrospirae, Planctomycetes, and Bacteroidetes, respectively. 13 CO2 labelling revealed that the contents of microbially incorporated soil organic carbon ( 13 C-SOC) and dissolved organic carbon were 0.572–1.45 mg kg −1 and 0.290–0.914 mg kg −1, respectively. Further, the 13 C-SOC correlated with the relative abundance of genes of the total six pathways, reductive citrate cycle, 3-hydroxypropionate bi-cycle, and reductive acetyl-CoA pathway. Another in situ labelling experiment showed a significant increase in δ 13 C of SOC, and the incorporated carbon ( 13 C) in SOC accounted for 3.85% of total atmospheric carbon absorption. These results showed that desert soil microbes containing genetic potential for autotrophic carbon fixation spread over a broad taxonomic range, and incorporated atmospheric carbon into organic components, which contributed to atmospheric carbon absorption. Although more research is required to accurately evaluate the portions of autotrophic carbon in the amount of atmospheric carbon absorption, the biotransformation of carbon from the atmosphere to soil via autotrophic carbon fixation represents a microbial pathway for persistent atmospheric CO2 absorption in desert soils, and further implicates an important carbon biochemical cycle for carbon accumulation in oligotrophic desert soils. Highlights: Autotrophic atmospheric carbon absorption in a semiarid desert was investigated. Desert soil microbes contain genomic of autotrophic carbon fixation. Autotrophic microbes in desert soils assimilate the atmospheric CO2 . Autotrophic process represents a microbial avenue for atmospheric CO2 absorption. Autotrophic process indicates an important cycle for carbon accumulation in desert.